Hubungan kemampuan komunikasi efektif tenaga medis terhadap kepuasan pasien - Detty, Ade Utia; Rizki, Fakhri; Liasari, Deni Eka (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: The quality of healthcare delivery can be improved by identifying current problems, and a key area to identify these problems is through customer satisfaction assessments. Many factors contribute to patient dissatisfaction in hospitals, one of which is communication from medical staff. Lack of communication between hospital staff and patients is a common complaint among patients in hospitals. Purpose: To analyze the relationship between effective communication skills of medical staff and patient satisfaction in hospitals. Method: This quantitative study used a cross-sectional design. The population was all patients at Bintang Amin Hospital. The sampling technique used was purposive sampling with a sample of 100 respondents. The instrument used was a questionnaire, and the statistical test used was the chi-square test. Results: The frequency distribution of effective communication was good (61%), and satisfaction (66%). The chi-square test result showed a p-value of 0.000 <0.05. Conclusion: There is a relationship between effective communication skills of medical staff and satisfaction. Keywords: Effective Communication; Medical Personnel; Patients; Satisfaction. Pendahuluan: Kualitas penyediaan pelayanan kesehatan dapat ditingkatkan dengan mendeteksi masalahnya saat ini, dan area penting untuk mengenali masalah tersebut melalui penilaian kepuasan pelanggan. Banyak faktor penyebab ketidakpuasan pasien di rumah sakit, salah satunya adalah faktor komunikasi dari tenaga medis. Kurangnya komunikasi antara staf rumah sakit dengan pasien merupakan salah satu alasan keluhan umum pasien di rumah sakit. Tujuan: Untuk menganalisis hubungan kemampuan komunikasi efektif tenaga medis terhadap kepuasan pasien di rumah sakit. Metode: Jenis penelitian kuantitatif dengan rancangan penelitian cross sectional, populasi adalah seluruh pasien di RS. Bintang Amin, teknik sampling yang digunakan adalah purposive sampling dengan sampel 100 responden. Instrumen menggunakan kuesioner dan uji statistic yang digunakan uji chi square. Hasil: Distribusi frekuensi komunikasi efektif (61%) baik, kepuasan (66%) puas. Hasil uji chi square p-value 0.000<0.05. Simpulan: Ada hubungan komunikasi efektif tenaga medis terhadap kepuasan. Kata Kunci : Komunikasi Efektif, Kepuasan, Tenaga Medis, Pasien